Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd007807.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for female subfertility

Abstract: Analysis 3.1. Comparison 3 Pentoxifylline versus placebo or no treatment/standard care, Outcome 1 Live birth; pentoxifylline vs placebo or no treatment/standard treatment (natural conceptions and undergoing fertility treatments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 110 publications
0
45
0
Order By: Relevance
“…Although, PCOS is considered as a hormonedependent disorder, recent evidence proposed the substantial role of oxidative stress (OS) and chronic low-grade inflammation in the pathogenesis of PCOS and its metabolic associations [1,4,5]. We have previously shown the role of oxidative and nitrosative stress and inflammatory responses (overproduction of cytokines) in the pathogenesis of hyperandrogenism-induced rat PCO [6,7].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although, PCOS is considered as a hormonedependent disorder, recent evidence proposed the substantial role of oxidative stress (OS) and chronic low-grade inflammation in the pathogenesis of PCOS and its metabolic associations [1,4,5]. We have previously shown the role of oxidative and nitrosative stress and inflammatory responses (overproduction of cytokines) in the pathogenesis of hyperandrogenism-induced rat PCO [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…It is estimated that 40% to 50% of cases of infertilities or subfertilities in couples are caused by female reproductive disorders [1]. Polycystic ovarian syndrome (PCOS) as a lifetime complex multigenic endocrinopathy is the leading cause of anovulatory infertility in women of reproductive age [2].…”
Section: Introductionmentioning
confidence: 99%
“…Only one article was removed over duplication. Further 18 articles were excluded (Bjelakovic et al, 2012;Chen & Lina, 2016;Consales et al, 2014;Farquhar et al, 2017;Garolla et al, 2014;Hart et al, 2015;Li et al, 2016;MacArthur et al, 2014;Nicoletti et al, 2016;Nisenblat et al, 2016;Pourmand et al, 2014;Povey et al, 2012;Rubes et al, 1998;Showell et al, 2013;Showell et al, 2014;Skalkidou et al, 2017;Van et al, 2017;Varshini et al, 2012) after reviewing the titles and abstracts. Full papers were obtained for the remaining 5 articles and reviewing were done thoroughly (Figure 1).…”
Section: Studies Selectedmentioning
confidence: 99%
“…[8][9][10][11] Recent studies showed a positive association between total antioxidant capacity and follicular fluid (FF) estradiol levels. 12,13 The FF total antioxidant capacity was higher in oocytes that successfully fertilized, but lower where the resultant embryo survived to transfer. [14][15][16] These studies reiterate the importance of oxidative stress in female reproduction.…”
Section: Introductionmentioning
confidence: 99%